2018
DOI: 10.1007/s40292-018-0279-7
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Density and Circulating Endothelial Progenitor Cells Before and After Treatment with Incretin Mimetics in Diabetic Patients

Abstract: Treatment with exenatide, but not with liraglutide, was able to increase the number of circulating EPCs, possibly through an antioxidative/antiinflammatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…We observed no difference between groups in CPCs, which include EPCs, and no significant change from baseline with liraglutide. A previous small study in 11 individuals with T2D, exploring the impact of GLP‐1RAs on the number of EPCs, reported an increase in EPCs with exenatide but not with liraglutide, consistent with our findings 14 . Although the authors of this previous study did not give specific reasons for this differential effect of the two GLP‐1RAs on the number of EPCs, they postulated that exenatide could exert a greater beneficial effect on the EPC pool through its anti‐inflammatory and antioxidant capabilities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed no difference between groups in CPCs, which include EPCs, and no significant change from baseline with liraglutide. A previous small study in 11 individuals with T2D, exploring the impact of GLP‐1RAs on the number of EPCs, reported an increase in EPCs with exenatide but not with liraglutide, consistent with our findings 14 . Although the authors of this previous study did not give specific reasons for this differential effect of the two GLP‐1RAs on the number of EPCs, they postulated that exenatide could exert a greater beneficial effect on the EPC pool through its anti‐inflammatory and antioxidant capabilities.…”
Section: Discussionsupporting
confidence: 92%
“…A previous small study in 11 individuals with T2D, exploring the impact of GLP-1RAs on the number of EPCs, reported an increase in EPCs with exenatide but not with liraglutide, consistent with our findings. 14 Although the authors of this previous study did not give specific reasons for this differential effect of the two GLP-1RAs on the number of EPCs, they postulated that exenatide could exert a greater beneficial effect on the EPC pool through its anti-inflammatory and antioxidant capabilities. Other placebo-controlled studies have shown conflicting effects of sitagliptin on the number of CPCs (including EPCs), with one study showing no effect, while another showed an increase in the CD34+/KDR phenotype only.…”
Section: Discussionmentioning
confidence: 92%
“…10,11 Exenatide is a commonly used clinical GLP-1 receptor (GLP-1R) agonist. A number of clinical trials that have been completed thus far have found that [12][13][14][15] exenatide can not only effectively reduce the blood glucose level of patients with T2DM but also has obvious effects other than hypoglycaemic effects, such as weight loss, lower blood pressure, blood lipid regulation, and improved endothelial dysfunction caused by hyperglycaemia and hyperlipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Exenatide is a commonly used clinical GLP-1 receptors (GLP-1R) agonist. A number of clinical trials that have been completed so far have found that [12][13][14][15] exenatide can not only effectively reduce the blood glucose level of patients with T2DM, but also has obvious effects other than hypoglycemic effects, such as losing weight, lowering blood pressure, regulating blood lipids, and improving endothelial dysfunction caused by hyperglycemia and hyperlipidemia. Studies have con rmed that GLP-1R are high expressed in mouse and human platelets [16].…”
Section: Introductionmentioning
confidence: 99%